1999
DOI: 10.1104/pp.121.2.399
|View full text |Cite
|
Sign up to set email alerts
|

The Starch-Debranching Enzymes Isoamylase and Pullulanase Are Both Involved in Amylopectin Biosynthesis in Rice Endosperm

Abstract: The activities of the two types of starch debranching enzymes, isoamylase and pullulanase, were greatly reduced in endosperms of allelic sugary-1 mutants of rice (Oryza sativa), with the decrease more pronounced for isoamylase than for pullulanase. However, the decrease in isoamylase activity was not related to the magnitude of the sugary phenotype (the proportion of the phytoglycogen region of the endosperm), as observed with pullulanase. In the moderately mutated line EM-5, the pullulanase activity was marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
174
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(185 citation statements)
references
References 30 publications
6
174
0
5
Order By: Relevance
“…In endosperm during grain fi lling of cereal plants, DBE probably play a crucial role in the starch synthesis (James et al, 1995, Nakamura et al, 1996Kubo et al, 1999;Burton et al, 2002;Dinges et al, 2003). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In endosperm during grain fi lling of cereal plants, DBE probably play a crucial role in the starch synthesis (James et al, 1995, Nakamura et al, 1996Kubo et al, 1999;Burton et al, 2002;Dinges et al, 2003). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are two types of DBE, pullulanase and isoamylase, that hydrolyze the α-1,6-glucosidic bond in amylopectin. In addition, it is accepted that DBE also plays an important role in starch synthesis (James et al, 1995;Nakamura et al, 1996;Kubo et al, 1999;Burton et al, 2002;Dinges et al, 2003). We examined the activity of pullulanase-type DBE in rice leaf sheath during the heading period (Fig.…”
Section: Effects Of the Amount Of Nitrogen On The Starch Content Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockouts of maize and rice pullulanases result in the loss of pullulanase activity (PA) without readily detectible phenotypic changes in plant growth or grain phenotypes 16,18 . Pullulanase function overlaps partially with the de-branching isoamylases and it has been reasoned that pullulanase knockouts are still viable because of activity of the isoamylases 16,19 .…”
mentioning
confidence: 99%
“…Both enzymes differ in their substrate specificity. Isoamylases can debranch glycogen, but scarcely attack pullulan, while pullulanase shows reverse specificity.Several studies have revealed that starch-debranching enzymes not only hydrolyze amylopectin in storage starch during germination, but also play essential roles in amylopectin biosynthesis (Ball et al, 1996;Kubo et al, 1999). In our previous studies, we revealed the distribution of starch-degrading enzymes in rice grains and their elution behavior during cooking with a specific antibody against each enzyme, including α-glucosidase, α-amylases, β-amylase, pullulanase and isoamylase, in Koshihikari cultivars (Tsuyukubo et al, 2010;Tsuyukubo et al, 2012).…”
mentioning
confidence: 99%